Effectiveness of Group Guidance Services Using Bibliotherapy Techniques to Increase Student Self-Resilience in Class IX Students of SMP Muhammadiyah 5 Bandar Lampung - Murni, Sri; Ismaniar, Ismaniar; Hazizah, Nur; Wismumpuni, Sidiq (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This study aims to analyze the effectiveness of group counseling services with bibliotherapy to increase the self-resilience of class IX students at SMP Muhammadiyah 5 Bandar Lampung. Resilience is a process that involves the role of various individual as well as social or environmental factors, where a person can reflect his own strength and toughness to rise from difficult experiences or situations that hinder the development of resilience components. The research method used in this research is quantitative method and this research is an experimental research with one group pretest-posttest design. In this study there were two groups, namely the first group as the experimental group, namely the group that was given treatment and the second group as the control group, namely the group that was not given treatment.The results of the study showed that group guidance services using bibliotherapy techniques could increase the self-reliance of class IX students at SMP Muhammadiyah 5 Bandar Lampung students. This is based on the self-resilience score of the experimental group that was given group guidance services using the bibliotherapy technique, which obtained 1396 with an average of 174.5. Whereas the control group that was not given group guidance services using the bibliotherapy technique obtained 1091 with an average of 136.3. Thus it can be concluded that group guidance services using bibliotherapy techniques can increase students' self-resilience.